An aberration of school effectiveness aas perceived by parents of secondary school students in Nigeria (2010)
The societal confidence in schools is one of the factors that is keeping the schools going. However, there are some bottlenecks associated with school effectiveness in Nigeria. One of them is examination malpractice. Therefore, this study examines the perception of Nigeria parents of secondary school students on examination malpractice as a stain in school effectiveness. A sample of 3, 289 parents of secondary schools students in Nigeria was used for the study. This study reveals that one of the factors that encourage examination malpractice in Nigeria is that questions set for students taking examination at senior secondary school certificate level are not related to the syllabus. Another one is the inadequate preparation of students by teachers. Parents contribute to examination malpractice by registering their children/ward in special centres where invigilators hardly get to during the conduct of examination. One of the potent consequences of examination malpractice is the frequent cancellation of examination results affecting innocent candidates. It is recommended that less emphasis should be placed on paper qualification; if this is done, it is likely that many of our students would do their work without resorting to examination malpractice.